2019
DOI: 10.1002/jmri.26949
|View full text |Cite
|
Sign up to set email alerts
|

Pattern recognition analysis of dynamic susceptibility contrast (DSC)‐MRI curves automatically segments tissue areas with intact blood–brain barrier in a rat stroke model: A feasibility and comparison study

Abstract: Background: The manual segmentation of intact blood-brain barrier (BBB) regions in the stroke brain is cumbersome, due to the coexistence of infarction, large blood vessels, ventricles, and intact BBB regions, specifically in areas with weak signal enhancement following contrast agent injection. Hypothesis: That from dynamic susceptibility contrast (DSC)-MRI alone, without user intervention, regions of weak BBB damage can be segmented based on the leakage-related parameter K 2 and the extent of intact BBB regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Although DCE-MRI is widely used for evaluating vascular permeability, previous studies have shown that DCE-MRI has limited sensitivity for evaluating subtle ischemic vascular permeability. 11,[28][29][30] A long DCE-MRI acquisition time ($20 min) would enhance the contrast as a result of the increased amount of extravasated CA. [31][32][33] However, extravascular extracellular space volume (v e ) and CA diffusion begin to affect the amount of extravasated CA over time and may not directly represent spatial vascular permeability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although DCE-MRI is widely used for evaluating vascular permeability, previous studies have shown that DCE-MRI has limited sensitivity for evaluating subtle ischemic vascular permeability. 11,[28][29][30] A long DCE-MRI acquisition time ($20 min) would enhance the contrast as a result of the increased amount of extravasated CA. [31][32][33] However, extravascular extracellular space volume (v e ) and CA diffusion begin to affect the amount of extravasated CA over time and may not directly represent spatial vascular permeability.…”
Section: Discussionmentioning
confidence: 99%
“…As it requires a certain amount of CA accumulation for T 1 values to change, its sensitivity may be limited in detecting subtle BBB damage, as in the early stage of ischemic stroke, within short DCE-MRI acquisition time (<10 min). 11 Dynamic susceptibility contrast (DSC)-MRI is a T 2 * -based or T 2 -based technique that is typically used for evaluating cerebral blood volume, cerebral blood flow (CBF), and mean transit time in capillaries. 12 DSC-MRI has a basic assumption that the CA is not extravasated from blood vessels, [13][14][15] but numerous studies have used the K 1 , K 2 model to study the effects of CA extravasation on the DSC-MRI signal in brains with BBB damage, especially for tumors and strokes.…”
Section: Introductionmentioning
confidence: 99%